AB1069 Burden of Refractory Gouty Arthritis among Difficult-To-Treat Patients over One Year: Post- HOC Analysis from Motion Observational Study. (10th June 2014) - Bessette, L.; Lioté, F.; Moragues, C.; Moericke, R.; Zhang, Z.; Ferreira, A.; Lecomte, P.; Kessabi, S.; Tian, H.; Li, L.; Singh, J.
Abstract : Background: Difficult-to-treat (DTT) patients were refractory gouty arthritis (RGA) patients with ≥3 gout attacks along with contraindication, intolerance or inefficacy to NSAIDs, colchicine or steroids included in the MOTION study. There is limited evidence on disease burden among this sub-population with few therapeutic options. Objectives: To assess the disease burden of gout in DTT patients over 1 year. Methods: This was a post-hoc subgroup analysis using MOTION data of RGA patients categorized into two groups 1) DTT patients 2) Other refractory gout (ORG) patients. DTT patients were further divided into 1) tophaceous gout patients (baseline tophi) 2) patients who discontinued ULT prior to study entry. Following outcomes were assessed at baseline, by time point and pooled yearly: health status by EuroQol Group 5 Dimension Questionnaire (EQ5D), disease-specific quality of life by Gouty arthritis Assessment Questionnaire Gouty arthritis Impact Scale (GAQ-GIS), health resource utilization, productivity loss, treatment satisfaction measured by Patient Global Assessment of Response to Treatment (PGART) and Investigator Global Assessment of Response to Treatment (IGART), and pain assessment. Summary statistics are presented for outcomes in each subgroup (mean for continuous variable and proportions for categorical variables). Results: A total of 64 out of 454 RGA patients were DTT patients (tophaceous gout: 29, discontinued ULT: 35) with mean age: 55.2 years and predominance of males (85.9%).DTT patients and tophaceous group had lower pooled mean EQ5D utility scores (0.78 and 0.65 vs 0.81) and EQ5D VAS scores (73.4 and 66.3 vs. 75.1) vs. ORG.Pain/discomfort was the most affected EQ5D domain across all groups with tophaceous group scoring least in all domains. Furthermore DTT patients expressed greater overall gout concern (76.5%) than ORG patients (72.4%); highest being for tophaceous group (85.5%) pooled yearly. Tophaceous group scored highest in all GAQ-GIS subscales among all groups. Resource utilization was higher for DTT patients vs. ORG patients with tophaceous group reporting highest emergency (55.2%), hospital (41.4%) and doctor visits (89.7%) over one year. Higher proportion of DTT patients missed working days due to gout vs. ORG patients at baseline line (23.4% vs. 15.6%). Patients and investigators in DTT group were less likely to be satisfied with current treatment. Higher percentage of DTT patients (45.3) experienced severe gout pain during the last flare vs. ORG patients (37.2%); highest being for tophaceous group (58.6) at baseline. Conclusions: Greater disease burden and resource utilization were experienced in DTT refractory gout patients with even worst outcomes in the tophaceous group. This confirms the high unmet medical need in DTT population. Disclosure of Interest: L. Bessette Grant/research support: Novartis, F. Lioté Shareholder of: Novartis, Ipsen, Sanofi, Grant/research support: unrestricted grants for the European Crystal Workshop and the first International conference on hyperuricemia and gout from Novartis, SOBI, Astra-Zeneca, Savient, Ipsen, Menarini, Mayoly-Spindler, Consultant for: Novartis, Ipsen, Menarini, Savient, Astra-Seneca, Mayoly-Spindler, C. Moragues Grant/research support: Novartis, R. Moericke Grant/research support: Novartis, Z. Zhang Grant/research support: Novartis, A. Ferreira Employee of: Novartis Pharmaceutical AG, P. Lecomte: None declared, S. Kessabi Employee of: Novartis Pharmaceutical AG, H. Tian Employee of: Novartis Pharmaceuticals Corporation, L. Li Employee of: Novartis Pharmaceuticals Corporation, J. Singh Grant/research support: Novartis, Takeda, Savient, Consultant for: Savient, Takeda, Regeneron, Allergan DOI: 10.1136/annrheumdis-2014-eular.4348